Enhancing Forecasting Capacities and Crop Capability Prediction Model/ Tool - Garanganga, Bradwell; Nyakutambwa, Trymore; Magagula, Futhi; Amha, Yosef; Bekele, Tamirat; Rutabingwa, Frank; Recha, John W.M. (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
The negative impact of hydro-meteorological hazards on the agricultural sector oftentimes leads to food insecurity, especially in Sub-Saharan Africa (SSA). It is, therefore, incumbent upon policymakers to formulate appropriate strategies to minimize hydro-meteorological hazards' effects on communities and economies. Increased availability of timely and tailored climate-related Knowledge, information, and products supports decision-makers in reducing climate-related losses and enhancing benefits. In this regard, regional partners1 commissioned a series of studies to develop and refine a crop capability prediction tool in order to maximize agricultural productivity while limiting the consequences of hydro-meteorological risks on the food system. This tool can assist policymakers and user communities decide on the most up-to-date crop capability based on seasonal climate forecast (SCF).